Effectiveness of Acupuncture on the Quality of Life in Allergic Rhinitis Patients: Meta Analysis - Widiatmaja, I Gusti Bagus Panji; Raharjo, Setyo Sri; Widyaningsih, Vitri (Indonesian Journal of Medicine, 2024)
Background:  Allergic rhinitis (AR) is one of the most common health problems experienced by people around the world. WHO ARIA defines allergic rhinitis as a disorder of the nose accompanied by symptoms of sneezing, runny nose, itching, and nasal congestion e after the nasal mucosa is exposed to allergens mediated by immunoglobulin E (IgE). Many studies have proven the impact of acupuncture on the immune system. This study aims to examine and estimate the effectiveness of acupuncture therapy for allergic rhinitis patients based on the results of previous similar studies. Subject and Method: This study is a systematic review and meta-analysis, with PICO as the following Population: allergic rhinitis patients. Intervention: acupuncture therapy. Comparison: sham/placebo acupuncture. Outcome: quality of life. The articles used in this study were obtained from several databases including Google Scholar, MEDLINE/PubMed, Science Direct, Hindawi, Europe PMC and Springer Link. These articles were collected for 1 month. The keywords to search for articles are as follows: "acupuncture for allergic rhinitis" OR "acupuncture for seasonal allergic rhinitis" OR "acupuncture for parenial allergic rhinitis" AND "quality of life" AND “randomized controlled trial". The article included in this study were a full text article with a randomized controlled trial  (RCT)  study design. Quality of life was measured using the Rhinitis Quality of Life Questionnaire (RQLQ). Meta analysis was written using PRISMA flow diagram and analyzed using Review Manager 5.4. Result:  A total of 9 RCT articles with a sample size of 2542 from Germany, Queensland, Victoria, China, and Korea were reviewed in this meta-analysis study. The results of data processing using the RevMan 5.4 application showed the effect of acupuncture therapy on the quality of life of allergic rhinitis patients. Acupuncture was able to lower RQLQ scores (improve quality of life), although it was not statistically significant. Allergic rhinitis patients who obtained acupuncture on average had a quality of life with an RQLQ score of 0.17 units, it was better than those getting sham acupuncture (SMD = -0.17; CI 95% = -0.40 to 0.05; p = 0.120). Conclusion:  There is an effect of acupuncture on the quality of life of allergic rhinitis patients.   Keywords: acupuncture, allergic rhinitis, quality of life, randomized controlled trial